2021
DOI: 10.1017/cts.2021.776
|View full text |Cite
|
Sign up to set email alerts
|

Value of peer mentoring for early career professional, research, and personal development: a case study of implementation scientists

Abstract: This version may be subject to change during the production process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 28 publications
1
20
0
Order By: Relevance
“…Being part of a K community also promotes peer mentoring, an important component of career growth and team building [16]. This sense of community was facilitated by a shared administration that continued to bring the different training programs together [4].…”
Section: Discussionmentioning
confidence: 99%
“…Being part of a K community also promotes peer mentoring, an important component of career growth and team building [16]. This sense of community was facilitated by a shared administration that continued to bring the different training programs together [4].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that peer review as a form of mentoring and support may be a critical mechanism for increasing the retention and success of early-career academics. Peer review offers not only mentoring and professional development but peer support in general also offers unique psycho-social benefits of emotional support from colleagues with shared experience and/or career stage (Cree-Green et al 2020, Dickson et al 2021. This unique benefit is particularly important for individuals from marginalized or under-represented groups in academia (Blackford 2018, Brommer & Eisen 2007, Eisen & Eaton 2017, Yadav & Seals 2019.…”
Section: Discussionmentioning
confidence: 99%
“…They engage in reciprocal constructive commentary in a supportive and encouraging manner with the ultimate desire of seeing each other attain an independent faculty position. Peer review programs are most well-known from their use in manuscripts (Rennie 2016, Tennant et al 2017, Tennant & Ross-Hellauer 2020, but see Haffer et al 2019, Murray et al 2018) and grant application review (Azoulay & Li 2020, Demicheli et al 2007, Marsh et al 2009 but see Lauer & Roychowdhury 2021, Witteman et al 2019, but have been successfully implemented in many other contexts for purposes of professional development and community building, especially for postdocs and early career researchers (Dickson et al 2021, Eisen & Eaton 2017, Kulage et al 2017.…”
Section: Introductionmentioning
confidence: 99%
“…Apart from being gender-skewed, their study did not reveal the extent to which ECRs' productivity was influenced by mentorship support. Other studies on mentorship and ECRs have looked at areas such as the mentorship needs of ECRs (Marino, 2021), the implementation of long-distance mentorship (Obi et al, 2021), and the value of peer mentorship (Dickson et al, 2021). While the academic employment opportunities worldwide are limited, two international surveys conducted in 2015 (Ghaffarzadegan et al, 2015) and 2017 (Woolston, 2017) found that approximately 78% and 75% of Ph.D. applicants wanted to work in academia, respectively.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Although it is claimed that mentorship has a favorable effect on a variety of outcomes, including the number of publications, academic advancement, faculty loyalty, and job happiness (Choi et al, 2019;Dickson et al, 2021), these claims are often not backed up with empirical research evidence. To date, the current literature reveals just one study (Olayide et al, 2021) that attempted to establish a connection between mentorship and research productivity.…”
Section: Literature Reviewmentioning
confidence: 99%